Quantitative Analysis of the Relationship between Income and Welfare of Tuna Fishermen from the Perspective of Sharia Finance - Ode, Santi; Hamizar, Arizal (PT. Anagata Sembagi Education, 2024)
This study aims to investigate the correlation between income levels and the welfare of fishermen operating in Waitomu Hamlet, Leihitu Subdistrict, Central Maluku Regency; and the relationship between the application of Sharia financial management principles with the income and welfare of tuna fishermen in that area. The research method applied is associative research, with research participants being actively operating fishermen in Waitomu Hamlet. The research approach involves the use of various techniques, including observation, distribution of questionnaires, and document analysis, with data analysis conducted using moment product correlation calculations. The results of the study revealed two main findings. First, the moment product correlation analysis showed a significant positive correlation between fishermen's income and the level of welfare, indicating that increasing income tends to have a positive impact on their welfare. Second, from a financial perspective, the practice of Sharia financial management applied by tuna fishermen in Waitomu Hamlet is considered successful.